Kosovo 2005/06: Phased independence? - Franz-Lothar Altmann (Stiftung Wissenschaft und Politik (SWP), 2005)
At the end of May, UNMIK chief Jessen-Petersen addressed the UN Security Council presenting a generally positive picture of the situation in Kosovo. Now, a special envoy of the UN Secretary General will prepare a full-length report by September 2005 that addresses whether the most important human rights and democratic standards in Kosovo have been fulfilled. It is expected that this report will ascertain that the necessary progress has been made so that, as early as this autumn, the UN Security Council can give the green light for starting negotiations on Kosovo's final status. Whether the carrot of EU membership can be dangled as the most enticing political incentive for Belgrade and Prishtina is questionable in light of the increasing wariness within the EU over expansion. (SWP Comments / SWP)
Keywords: 320